Novel Antiplatelet Agent Use for Acute Coronary Syndrome in the Emergency Department: A Review - M. Curial; E. Nath; E. Lang (Cardiology Research and Practice)
Background. Acute Coronary Syndrome (ACS) is a clinical condition encompassing ST Segment Elevation Myocardial Infarction (STEMI), Non-ST Segment Elevation Myocardial Infarction (NSTEMI), and Unstable Angina (UA) and is characterized by ruptured coronary plaque, ischemic stress, and/or myocardial injury. Emergency department (ED) physicians are on the front lines of ACS management. The role of new antiplatelet agents ticagrelor and prasugrel in acute ED management of ACS has not yet been defined. Objective. To critically review clinical trials using ticagrelor and prasugrel in the treatment of ACS and inform practitioners of their potential utility in treating ACS in the ED. Results. Trials on the efficacy of ticagrelor and prasugrel achieve statistical significance in decreasing composite endpoints in select patient populations. Conclusion. The use of ticagrelor and prasugrel as first line ED treatment of ACS is not well established. Current evidence supports the use of several agents with the final decision based on treatment protocols conjointly developed between cardiology and emergency medicine (EM). Further clinical trials involving head-to-head trials or comparisons of drug-based strategies are required to show superiority in reducing cardiac endpoints with regard to ED initiation of treatment.